Distribución salarial y educación en Lima Metropolitana, 1970-1984 - Rodriguez, José (1991)
This paper evaluates tbe effects of educational expansion on the wage distribution in Metropolitan Lima from 1970 to 19I34. The analysis is based on the dynamic decomposition of the second inequality measured proposed by Theil -the Theil-L-, and makes use of peruvian household surveys. The main results suggest that such effects depend on the kind of educational expansion that takes place, and that they not necessarily contribute to improve the distribution.